2011
DOI: 10.1038/ja.2011.16
|View full text |Cite
|
Sign up to set email alerts
|

Spoxazomicins A–C, novel antitrypanosomal alkaloids produced by an endophytic actinomycete, Streptosporangium oxazolinicum K07-0460T

Abstract: Three novel antitrypanosomal alkaloids, named spoxazomicins A-C, were isolated by silica gel column chromatography and HPLC from the culture broth of a new endophytic actinomycete species, Streptosporangium oxazolinicum K07-0460 T . The structures of the spoxazomicins were elucidated by NMR and X-ray crystal analyses and shown to be new types of pyochelin family antibiotic. Spoxazomicin A showed potent and selective antitrypanosomal activity with an IC 50 value of 0.11 lg ml À1 in vitro without cytotoxicity ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

7
3

Authors

Journals

citations
Cited by 89 publications
(57 citation statements)
references
References 9 publications
1
54
0
2
Order By: Relevance
“…As a result, we found the actinoallolides which are 12-membered macrolides in a cultured broth of Actinoallomurus fulvus MK10-036, the trehangelins which consist of two trehalose molecules and an angelic acid from Polymorphospora rubra K07-0510, and the spoxazomicins, pyochelin family antibiotics from Streptosporangium oxazolinicum K07-0460 T . [39][40][41] Furthermore, we have cultured 22 endophytic actinomycetes, which were isolated from eight kinds of plant and classified in 12 genera. The HPLC analyses of their culture broths extracted by ethyl acetate indicated that aranciamycins were produced in seven strains, belonging to the genera Sphaerisporangium, Kibdelosporangium, Planomonospora and Actinophytocola, and their cultured broths displayed antibacterial activity against Xanthomonas campestris pv.…”
Section: Search For Novel Compound From Endophytic Actinomycetesmentioning
confidence: 99%
“…As a result, we found the actinoallolides which are 12-membered macrolides in a cultured broth of Actinoallomurus fulvus MK10-036, the trehangelins which consist of two trehalose molecules and an angelic acid from Polymorphospora rubra K07-0510, and the spoxazomicins, pyochelin family antibiotics from Streptosporangium oxazolinicum K07-0460 T . [39][40][41] Furthermore, we have cultured 22 endophytic actinomycetes, which were isolated from eight kinds of plant and classified in 12 genera. The HPLC analyses of their culture broths extracted by ethyl acetate indicated that aranciamycins were produced in seven strains, belonging to the genera Sphaerisporangium, Kibdelosporangium, Planomonospora and Actinophytocola, and their cultured broths displayed antibacterial activity against Xanthomonas campestris pv.…”
Section: Search For Novel Compound From Endophytic Actinomycetesmentioning
confidence: 99%
“…This research will be reported in the accompanying paper. 7 The strain K07-0460 T was phylogenetically identified as being a member of the genus Streptosporangium described by Couch. 8 At present, the genus Streptosporangium comprises 15 species and 2 subspecies: Streptosporangium roseum, 8 S. amethystogenes subsp.…”
Section: Introductionmentioning
confidence: 98%
“…[2][3][4][5] This time we focused on metabolites from cultures of cordyceps that showed antitrypanosomal activity. The "dong chóng xìa căo" in Chinese pronunciation, means "summer herb-winter worm" is traditionally used for herbal medicines and health foods in East to Southeast Asia.…”
Section: In Vitromentioning
confidence: 99%